Fat chance in a thin world - Chalow, Thea (Boston, Mass. : WBGH Educational Foundation, 1983)
Examines why some people get fat and others do not. Physicians, psychologists, professors, and researchers tell of their findings and overweight people personalize the relevance of these clinical investigations
Keywords: Obesity; Weight control